ANALYSIS OF ENVIRONMENTAL DISASTER MITIGATION ON REMPANG ISLAND : EVALUATION AND CANCELLATION OF NATIONAL STRATEGIC DEVELOPMENT POLICY - Tauhid Ma’rifatullah; Yustina Yustina (PT. Jurnal Center Indonesia Publisher, 2026)
The conflict surrounding the Rempang Eco-City National Strategic Project (PSN) on Rempang Island, Batam City, Riau Islands Province, is one of the most complex development policy crises of the past decade. This study analyzes the neglected environmental disaster mitigation dimensions in the acceleration of the Rempang Eco-City PSN from nine environmental perspectives, while evaluating whether the cancellation of this strategic development policy is a normatively and empirically justifiable choice. Using a qualitative research approach with a case study design, the study combines regulatory analysis based on legal documents including Laws, Government Regulations, Presidential Regulations, Ministerial Regulations, Environmental Impact Assessment (AMDAL) documents, and the Batam City Spatial Plan (RTRW) with field data from secondary sources compiled between 2023–2025. The findings reveal four main conclusions: (1) regulatory incoherence exists between Permenko Ekuin No. 7/2023 and Law No. 32/2009 on Environmental Protection and Management (PPLH) as well as Law No. 27/2007 on Coastal Zone Management; (2) the AMDAL process was carried out procedurally without participatory substance and was only initiated after the conflict erupted; (3) environmental impacts including threats of deforestation of protected forests, mangrove ecosystem degradation, and sea sand exploitation have not been adequately mitigated; and (4) resistance from approximately 80% of affected residents indicates a failure of the Free, Prior, and Informed Consent (FPIC) principle. The most recent development shows that through Presidential Regulation (Perpres) No. 12 of 2025, signed by President Prabowo Subianto on February 10, 2025, Rempang Eco-City is no longer listed among the 77 national strategic projects. This study recommends a comprehensive policy evaluation for Rempang Island development based on an independent AMDAL review, fulfillment of the rights of the Malay indigenous community, and a moratorium on all construction activities until legal certainty is established.